Analysis of the application of physics in the design and construction of architectural projects. The Eiffel Tower (2021)
This article studied the impact and application of physical concepts in the design and construction of the Eiffel Tower in Paris, an architectural reference that implemented physical concepts in its structural design. A documentary methodological framework was used to establish the importance of the Eiffel Tower in the universal exposition of Paris in 1989 and, to carry out the structural analysis of the work; a quantitative-descriptive approach was used for the recognition of the basic concepts of physics from architecture according to gender, through a survey as a research instrument developed under non-probability and convenience sampling, which was applied to students of Architecture of the Universidad Francisco de Paula Santander, Colombia, in order to determine the knowledge of basic physics by students. The results of this research showed that the Eiffel Tower represents a milestone in architecture where physical concepts such as tension, compression, traction, aerodynamics, and torque were applied. Finally, it was evidenced that the students who participated in this study recognize the importance of applying the basic concepts of physics in architecture; fact by which it is recommended to encourage the study of physics, to strengthen the technological component of Architecture.